A Retroperitoneal Paraganglioma Presenting as Acute Coronary Syndrome: A Rare Case Report and Literature Review - Abhishek Mishra; Shalendra Singh; Ankit Mathur; Anil Kumar Abbot (Heart Views)
Paragangliomas are catecholamine-secreting tumors arising from the sympathetic and parasympathetic ganglia. Here, we describe a case in which a young man who had visited the emergency room complaining of headache and shortness of breath was later found to have acute coronary syndrome with accompanying cardio-pulmonary complications necessitating immediate cardiac intervention. Later on, during further management, he was diagnosed with a retroperitoneal paraganglioma. Thus, we try to emphasize the need for a high clinical index of suspicion and urgent radio-imaging for diagnosing this relatively rare clinical entity to prevent fatal outcomes or any long-term morbidity.